2016
DOI: 10.1016/j.jpainsymman.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sudden Death in Palliative Care: Data From the Australian Palliative Care Outcomes Collaboration

Abstract: This study quantifies rates of sudden death in hospice/palliative care and has implications for conversations about prognosis between clinicians, patients, and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 28 publications
2
24
1
4
Order By: Relevance
“…There is a cohort of people with life-limiting illnesses who experience sudden death, but that cohort should not be reflected in these data. 39,40 However, these patients were not removed from the dataset as they do constitute part of the whole, with the small numbers observed as having reasonable performance status not affecting the overall models.…”
Section: Discussionmentioning
confidence: 99%
“…There is a cohort of people with life-limiting illnesses who experience sudden death, but that cohort should not be reflected in these data. 39,40 However, these patients were not removed from the dataset as they do constitute part of the whole, with the small numbers observed as having reasonable performance status not affecting the overall models.…”
Section: Discussionmentioning
confidence: 99%
“…Kematian mendadak merupakan kasus kematian yang terjadi tanpa adanya keluhan kesehatan sebelumnya sehingga tidak diketahui penyebab kematiannya, dan kejadian kematian mendadak paling tinggi terjadi pada saat di rumah. 1,2 Menurut World Health Organization (WHO), kematian mendadak adalah kematian yang terjadi dalam 24 jam dari munculnya tanda-tanda gejala penyakit. Pada kasus-kasus forensik kematian mendadak terjadi dalam hitungan menit atau bahkan detik sejak gejala pertama timbul dan terjadi tidak terduga.…”
Section: Pendahuluanunclassified
“…Pada data penelitian yang dikumpulkan oleh spesialis paliatif layanan perawatan dari hasil kolaborasi perawatan paliatif di Australia melalui studi kohort berturut-turut secara prospektif diperoleh 13.966 kasus dengan rerata usia 40-70 tahun. 2 Perbedaan beberapa penelitian yang telah dipaparkan hanya pada pengelompokan usia saja, sedangkan hasil penelitiannya serupa dengan penelitian ini, yaitu kelompok usia terjadinya kematian mendadak tersering ialah usia 20-60 tahun.…”
Section: Bahasanunclassified
“…In the weeks prior to death in a palliative care population, the prevalence and intensity of breathlessness is reported to increase and functional status most often worsens [7,8]. This phenomenon has been described in several datasets and includes people with a wide range of recorded causes of death, including frailty, dementia and those perceived to have had a "sudden" death [9][10][11][12]. To date, two cohort studies have proposed contradictory effects of performance status on chronic breathlessness at the end of life: one suggested that decreasing performance status is associated with the increasing breathlessness and the other, the opposite [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between breathlessness and functional status at the end of life is important to inform clinical discussions with concerned patients and their relatives, and to guide research in ways of best palliating breathlessness. At least two distinct trajectories of function and their relation to breathlessness need to be understood: 1) progressive functional decline and 2) sudden deterioration in the setting of a known life-limiting illness [9,12]. Such patterns may also provide important insights into the underlying pathologies leading to different trajectories of dying and the need to pay heed to symptom exacerbations even in the last weeks of life.…”
Section: Introductionmentioning
confidence: 99%